WOMEN IN PRIVATE PRISON: HEALTH CARE - Graziele Cardoso de Almeida, Débora; Quitéria Fernandes Ferreira, Ana; Pereira Soares, Daniele; Kelly Paes, Gracy; Arthur Guimarães dos Santos, José; da Silva Fidelis, Laysa; Carolina Salustino dos Santos, Maria; Claudino do Nascimento, Nathalia (Health and Society, 2023)
The lack of health care is one of the most serious aspects that affect the Brazilian prison system. The environment of the penal establishment contributes to the emergence of latent diseases, or their manifestation. The convicts are not able, by their own means, to seek care or medication other than that offered by the system. In the case of female incarceration, the situation is more serious, since there is no specific policy for the care of imprisoned women, especially when pregnant. The objective is to reflect on the assistance to Women’s Health in the Prison System. The policies so far designed to improve the health conditions of female prisoners are undeniably worthy of recognition, as they are attentive to issues that are, in fact, more alarming. However, the biggest challenge is its implementation.